Freezing of edible flowers: Effect on microbial and antioxidant quality during storage - Fernandes, Luana (2018)
Edible flowers are a new gourmet product; however, they are not always available all years. Thus, it is essential to find out technologies to guarantee this product for a longer time. Flowers of four species (borage [Borago officinalis], heartsease [Viola tricolor], kalanchoe [Kalanchoe blossfeldiana], and dandelion [Taraxacum officinale]) were subjected to freezing (in their natural form and in ice cubes) and analyzed in terms of visual appearance, the content of flavonoids, hydrolysable tannins, phenolics, antioxidant activity (2,2-diphenyl-1-picrylhydrazyl radical scavenging activity and reducing power), and microbial quality after storage for 1 and 3 months. Flowers in ice cubes showed similar appearance to fresh ones during the 3 months of storage, whereas frozen flowers were only equivalent up to 1 month with the exception of kalanchoe. Even though flowers in ice cubes showed good appearance after 3 months of storage, they had the lowest values of bioactive compounds and antioxidant activity. On the contrary, when frozen, the content of bioactive compounds maintained or even increased up to 1 month of storage compared to fresh flowers, except for borage. Furthermore, in both freezing treatments, the microorganisms’ counts decreased or maintained when compared to fresh samples, except in dandelion. In general, both treatments may allow keeping the flowers after their flowering times.